Dilemmas of identity, new public management and governance : selected papers from the 11th international research conference, hosted by Luleå University of Technology, Department of human work science, Friday 31th August-Saturday 1st September 2007 - Berg, Elisabeth; Barry, Jim; Piippola, Saila; Chandler, John (Luleå tekniska universitet, Arbetsvetenskap, 2008)
This Conference is organized jointly with Staffordshire University and the University of East London, and provides a forum for policy, organizational and critical sociological analyses of the human services including health, social services, housing, education and the voluntary sector. Although the theme of this year's conference concerned governance and new public management and its relationship to identities in the public and voluntary sectors, many of the papers focus on identities from different perspectives rather than having their focus on governance or new public management. It might be argued that governance and new public management have become a part of everyday life in these sectors, but the processes of change engendered raise important questions around issues of identities within human services, not least the degree to which they reflect, or conversely impact on, the discourses at work. As in the past, the aim is to provide a forum for both new and established researchers to share ideas in a supportive and scholarly environment. A wide range of contributions are encouraged, including country-specific and cross-cultural research. Godkänd; 2008; 20080519 (biem)